Race, Body and Art: contributions of black artists to reinvent the world: contribuciones de artistas negros para reinventar el mundo (Revista Apotheke, 2021)
In this article we discuss the contribution of African and Afro-descendant black artists in the debate on reinventing the world. From analyzing the works of Michael Armitage, Frida Orupabo and Rosana Paulino, we problematize the way artists work out violences that affect the black body while results from colonialism, racism and enslavement. The dialogue with these works allows us to affirm the importance of the Afro-diasporic art for tensioning racist practices that persist currently, a condition for reinventing the world.
Keywords: race; body; poliics; afro-diasporic art